Remedial Aspect of Zinc Oxide Nanoparticles Against Serratia Marcescens and Enterococcus Faecalis - Djearamane, Sinouvassane; Loh, Zhe Chi; Lee, Jun Jie; Wong, Ling Shing; Rajamani, Ranjithkumar; Luque, Priscy Alfredo; Gupta, Piyush Kumar; Liang, Sharolynne Xiao Tong (Frontiers in Pharmacology, 2022)
Zinc oxide nanoparticles (ZnO NPs) have been widely used in biomedical applications due to their high biocompatibility and low toxicity to humans. The present work aimed to investigate the antibacterial effects of different concentrations of ZnO NPs on two opportunistic pathogens, Serratia marcescens and Enterococcus faecalis. The surface interaction between nanoparticles and bacterial cell wall, and the subsequent morphological alterations on the bacterial surface, were examined through Fourier transform infrared spectroscopy and scanning electron microscope. The energy dispersive X-ray analysis was used to confirm the elemental composition of ZnO NPs and the cellular accumulation of ZnO NPs in bacteria. The growth-inhibitory test demonstrated a dose-dependent growth inhibitory effect of ZnO NPs against both the test bacteria, as the higher concentration of nanoparticles caused the higher bacterial growth inhibition. The results showed that ZnO NPs caused a higher growth inhibition (63.50 ± 2.50%) on the Gram-positive bacterium E. faecalis compared to the Gram-negative bacterium S. marcescens (51.27 ± 4.56%). Fourier transform infrared spectrum revealed the possible involvement of hydroxyl, carboxyl, amides, methylene, and phosphate groups from the biomolecules of bacterial cell wall such as proteins, carbohydrates, lipids, and phospholipids in the interaction of ZnO NPs on bacterial cell surface. Energy dispersive X-ray analysis showed the higher accumulation of ZnO NPs in E. faecalis than S. marcescens analogous to the bacterial growth inhibition. Scanning electron microscopy images confirmed the antibacterial properties of ZnO NPs, showing the loss of integrity of cell membrane and distortion of bacterial cells. Hence, the potential of ZnO NP as an antibacterial agent against S. marcescens and E. faecalis has been confirmed.